The Influence of Teacher Questions to Stimulate Students’ Active Participation and Engagement in Non-Formal EFL Speaking Classes - Safitzal Fajar Rahmawati; Endang Fauziati; Sumardi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study evaluates how teacher questions influence active participation and engagement in non-formal EFL speaking classes. The objective is to determine the effectiveness of different question types in promoting student interaction and improving language learning. A qualitative case study design was employed in two classes at a private English course in Madiun, Indonesia, involving 2 English teachers and 24 elementary students with basic to lower-intermediate proficiency. Data were collected during 3 months (December-February) through classroom observations, digital audio recordings, field notes, and semi-structured interviews with both teachers and students. The analysis focused on categorizing teacher questions into display/closed-ended, yes/no, and referential/open-ended types, and examining the effect on individual and choral student responses. Findings indicate that display/closed-ended and yes/no questions effectively stimulate immediate recall and maintain classroom focus, while referential/open-ended questions encourage deeper cognitive engagement and personalized expression. The results suggest that a balanced approach to questioning not only stimulates immediate recall but also transforms passive learners into active participants, improving students’ communication competence. It also implies that the teacher should have more variations such as combine three kinds of those questions for engaging students to have an active participation through questions.